2010
DOI: 10.1016/j.ophtha.2010.01.037
|View full text |Cite
|
Sign up to set email alerts
|

Doxycycline's Effect on Ocular Angiogenesis: An In Vivo Analysis

Abstract: Purpose To determine the in vivo effect of doxycycline (doxy) on choroidal angiogenesis and pterygium growth by using a choroidal neovascular murine model (CNV), a directed in vivo angiogenesis assay (DIVAA) and a pterygium murine model. Design Experimental Study Participants 3 murine models were investigated with 4 mice minimum per group and 22 maximum per group. Methods Mice received water with or without doxycycline (Leiter's Pharmacy, San Jose, CA). For the CNV, the neovascular lesion volume was dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 36 publications
2
33
0
3
Order By: Relevance
“…Doxycycline has also been reported to dose-dependently reduce laser-induced CNV lesions in mice, as shown in this study as well (9,11,12), and preliminary observations suggest a beneficial effect of doxycycline in treating neovascular AMD. One study suggests that this effect may be mediated by increased FasL expression by RPE cells after doxycycline treatment (11).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Doxycycline has also been reported to dose-dependently reduce laser-induced CNV lesions in mice, as shown in this study as well (9,11,12), and preliminary observations suggest a beneficial effect of doxycycline in treating neovascular AMD. One study suggests that this effect may be mediated by increased FasL expression by RPE cells after doxycycline treatment (11).…”
Section: Discussionsupporting
confidence: 80%
“…4B). Importantly, several studies have shown that doxycycline dose-dependently inhibits CNV lesion formation in this model, demonstrating a potent antiangiogenic activity of doxycycline (9,11,12). Thus, we hypothesized that inhibition of M2-type macrophage polarization by doxycycline results in reduced proangiogenic cytokine expression and subsequent neovascularization in this model.…”
Section: Doxycycline Inhibits M2-type Macrophage Polarization Inducedmentioning
confidence: 90%
“…tarafından yapılan bir çalışmada, oral doksisiklin verilmiş olan tavşanlarda lazer ile indüklenmiş korneal NV'nin gerilediği gösteril-miştir. 73 …”
Section: Matriks Metalloproteinaz İnhibitörleriunclassified
“…Adenovirüs taşıyıcı ile sağlanan çVEGFR-1 ve çVEGFR-3 salınımındaki artışın hayvan korneasında NV'yi engellediği gösterilmiştir. 73 Nonviral yöntemler daha güvenlidir, ancak daha kısa etki süreleri vardır. Çift sarmallı small interfering RNA (siRNA), plazmidlerden daha küçük olup, subkonjonktival enjeksiyon sonrası korneal hücrelerin içine girerek mRNA'lara spesifik olarak bağlanır.…”
Section: Vegf Dışındaki Anjiyogenez Stratejileriunclassified
“…However, when tet-on system is used, DOX must be administered in the drinking water of mice, which can be rather expensive. In addition, DOX inhibits angiogenesis in mouse (Cox et al, 2010;Fainaru et al, 2008). In our lab, the DOX-treated murine hearts (1mg/ml in the drinking water) tend to be ~30% smaller compared to the age-matched untreated hearts (data not shown).…”
Section: A Potential Lineage Tracing Study To Monitor Contribution Ofmentioning
confidence: 99%